EFEKTIVITAS PEMBELAJARAN OUTDOOR STUDY DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Kiki Dwi Hapsari; Herkulana Herkulana; Achmadi Achmadi (Universitas Tanjungpura, 2020)
Abstract This research aimed to determine the effect of effectiveness of outdoor study in increasing student learning outcomes on economics in the 11’th grade of SMA Negeri 7 Pontianak. The research method used in this study was an experiment with the form of quaisy experiment. The population in this study was all students of XI IPS SMA Negeri 7 Pontianak. These samples of research are all students of class XI IPS 4 as experiment class and XI IPS 2 as control class. Sampling technique used purposive sampling. The data collection technique used observation and test. The results showed that there was an influence between outdoor study learning on student learning outcomes in XI IPS class of SMA Negeri 7 Pontianak. Based on descriptive analysis, the control class has an average pre-test score 62,35 and post-test score 70,29. Meanwhile, the experiment class has an average pre-test score 63,24 and post-test score 79,56. For t test, a significance value of 0,010 was obtained with an effect size value of 63% which is the medium category. Keywords: Learning, Learning Outcomes, Outdoor Study